2014
DOI: 10.1517/17425255.2014.894020
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 pharmacogenetics in African populations: implications for public health

Abstract: The variability in the pattern of genetic variation between populations translates into differences in drug response. Understanding CYP variability improves rational drug use and has public health significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 110 publications
1
58
0
Order By: Relevance
“…Effective antiretroviral (ARV) therapy largely depends on adequate drug exposure to suppress viral replication and allow the immune system to recover (Panel on Antiretroviral Guidelines for Adults and Adolescents, 2009). However, approximately 35% of HIVinfected patients on HAART still fail to achieve durable virological suppression, while 45%-80% of those who do achieve virological suppression develop toxicities related to the ARV drugs (Cressey and Lallemant, 2007;Dandara et al, 2014a;Smyth et al, 2012;World Health Organization, 2010). These differences in treatment outcomes are attributed to inter-individual differences in the metabolism of ARV drugs (Pozniak et al, 2011;Rivero et al, 2007).…”
mentioning
confidence: 99%
“…Effective antiretroviral (ARV) therapy largely depends on adequate drug exposure to suppress viral replication and allow the immune system to recover (Panel on Antiretroviral Guidelines for Adults and Adolescents, 2009). However, approximately 35% of HIVinfected patients on HAART still fail to achieve durable virological suppression, while 45%-80% of those who do achieve virological suppression develop toxicities related to the ARV drugs (Cressey and Lallemant, 2007;Dandara et al, 2014a;Smyth et al, 2012;World Health Organization, 2010). These differences in treatment outcomes are attributed to inter-individual differences in the metabolism of ARV drugs (Pozniak et al, 2011;Rivero et al, 2007).…”
mentioning
confidence: 99%
“…Despite the similarity in allele and genotype frequencies for the CYP2B6 g.15582C > T SNP between South Africans, Cameroonians, Yoruba, and African-Americans, previous studies have shown that differences in minor allele frequencies for SNPs exist between these populations (Swart et al, 2012). African populations are, however, consistently shown to be significantly different from European and Asian populations (Dandara et al, 2014b) and this has major implications for personalised medicine in Low-and MiddleIncome Countries (LMIC).…”
Section: Resultsmentioning
confidence: 99%
“…I dentification of genetic variation that is of pharmacogenomics (PGx) relevance in African populations is an enormous endeavour and will continue to be a research priority in the next decade (Dandara et al, 2014a;2014b). Although there is an explosion in the generation of human DNA sequences using next generation sequencing (NGS) technologies, the accessibility of these technologies in the developing world is severely limited.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic profiles based on these studies are then extrapolated for use in other populations, despite the fact that variant frequencies can differ markedly between different populations (Ikediobi et al, 2011). Dandara et al (2014) provide a review on the importance of CYP450 pharmacogenetics in African populations and the implications for public health. The authors highlight that a large number of ethnic groups need to be characterized to capture the full Population based dosing results in standard dosing levels being representative of the level required by EM individuals.…”
Section: Pharmacogenetics In Africamentioning
confidence: 99%
“…The review by Dandara et al (2014) provides a summary of efavirenz metabolism and CYP2B6 pharmacogenetics in African populations, specifically the effect of the CYP2B6 516G4T variant. However, other CYP2B6 polymorphisms may also play a role in altered enzyme activity, as may polymorphisms in CYP2A6 and UGT2B7.…”
Section: Pharmacogenetics and Hiv Therapymentioning
confidence: 99%